Promoting learning practices: moving towards innovation - Frigerio, Chiara (2006)
As many authors have stated, the importance of organizational learning is fundamental in order to gain competitive advantage and survive in a turbulent environment. Many learning models have been studied in recent years. They have been used to analyze practices or aspects of learning in many industries. This paper aims to develop a particular framework in order to understand the determinants for organizational learning, depending on the firm’s general approach towards information and knowledge management. The theoretical framework is derived from Blackler and McDonald’s study, which focused on organizational learning approaches, and from Duncan and Weiss’s work, which studied attitudes towards knowledge management. This is applied to a particular context characterized by a high level of bureaucracy: the Italian banking industry. In particular, the study is conducted on a sample of 54 banks. The empirical analysis is carried out through questionnaires and interviews. Data is analyzed using statistical analysis. Results are shown and empirical implications are discussed, also in order to explain the reasons for the current situation.